Endocrinologic, morphologic, and pregnancy assessment of intact and sliced ovarian orthotopic transplantation without a vascular pedicle - Petroianu , Andy; Alberti , Luiz Ronaldo; Vasconcelos , Leonardo de Souza (Brazilian Journal of Transplantation, 2007)
Objective: The purpose of the present work was to assess endocrine and hystological ovarian aspects following allogeneic ovarian transplantation without vascular pedicle. Method: 32 female New Zealand White and California rabbits were studied. In Group 1- Control (n=8), only laparotomy and laparorrhaphy was carried out. In Group 2A (n=8) ovarii were orthotopically transplanted from the rabbit of one race to one of the other race and vice-versa integer in both sides. In Group 2B (n=8) the ovarii were sliced and orthotopically transplanted. In Group 2C (n=8), in one side the ovary was transplanted integer and in the other side it was sliced. Cyclosporine was administered every day in all animals of group 2. 3 months later, the animals were paired with sexually mature males for copulation. Estradiol, progesterone, FSH and LH levels were assessed. Histologic study of the transplanted ovaries, tubes and uterii were carried out. Chi-square test compared the occurrence of pregnancy and the birth of litters. One-way ANOVA and Tukey-Kramer Test compared the hormonal dosages. Results: Pregnancies occurred in all rabbits of Group 1, between the second and third months after copulation. In Group 2, the pregnancies were verified between the forth and eighth postoperative months. Pregnancies were present in 37.5% of rabbits in Group 2A, 50% in group 2B and 62.5% in group 2C. The hormone levels and histology confirmed the vitality of all ovaries. Conclusions: Allogeneic ortothopic ovarian transplantation without vascular pedicle was effective to preserve normal level of ovarian hormone and to allow natural pregnancy.